2010
DOI: 10.4314/as.v8i2.51100
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic assessment of some sweet potato varieties for intercropping with pigeonpea in southern guinea savanna of Nigeria

Abstract: Field experiments were conducted at the National Root Crops Research Institute sub-station, Otobi, in 2006 and 2007 to assess the suitability of improved sweet potato varieties for intercropping with pigeonpea and also to determine the planting pattern and the productivity of the intercropping system. Intercropping decreased total fresh root and saleable root yields of sweet potato when mixed or row-intercropped with pigeonpea. All intercropping combinations of sweet potato varieties and pigeonpea had land equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
4
9
0
Order By: Relevance
“…Villareal and Hsu (1982), and Byamukama et al (2007) reported variation in sweetpotato root yields across seasons and attributed it to seasonal weather variations. The decline in root and biomass yields observed in the present study, with the increasing maize plant populations, is in agreement with previous studies on sweetpotato (Egbe and Idoko, 2009;Ossom, 2010) and potatoes (Ebwongu et al, 2001). While studying sweetpotato-pigeonpea intercropping, Egbe and Idoko (2009) observed declining fresh root yield across five sweetpotato varieties.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Villareal and Hsu (1982), and Byamukama et al (2007) reported variation in sweetpotato root yields across seasons and attributed it to seasonal weather variations. The decline in root and biomass yields observed in the present study, with the increasing maize plant populations, is in agreement with previous studies on sweetpotato (Egbe and Idoko, 2009;Ossom, 2010) and potatoes (Ebwongu et al, 2001). While studying sweetpotato-pigeonpea intercropping, Egbe and Idoko (2009) observed declining fresh root yield across five sweetpotato varieties.…”
Section: Discussionsupporting
confidence: 81%
“…The decline in root and biomass yields observed in the present study, with the increasing maize plant populations, is in agreement with previous studies on sweetpotato (Egbe and Idoko, 2009;Ossom, 2010) and potatoes (Ebwongu et al, 2001). While studying sweetpotato-pigeonpea intercropping, Egbe and Idoko (2009) observed declining fresh root yield across five sweetpotato varieties. The decline was attributed to reduced photosynthesis by sweetpotato leaves, due to reduced solar radiation interception by shading from the taller pigeonpea plants.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The depression was severe on both intercrop components, as intercrop yields fell below 50% of sole crop values in most instances. Yield reduction is common in most intercrop studies of sweet potato and tall legumes and cereals (Egbe, 2012;Egbe and Idoko, 2009;Belehu, 2003). These authors opined that sharing growth resources among component crops under intercropping could limit growth and accumulation of dry matter compared to sole cropping where competition exists.…”
Section: Discussionmentioning
confidence: 99%
“…According to Davis and Wooley (1993), the traits required for intercropping are those which enhance the complimentary effect between species and minimize the intercrop competition. Egbe and Idoko (2009) observed that sweet potato varieties commonly cultivated by farmers in Southern Guinea Savannah zone of Nigeria often result in low root yield (3-9 t/ha) compared to the average world yield of 14.9 t/ha (FAO,2001). Yield advantages of intercropping sweet potato with some crops ( maize, okra, pigeonpea) have been reported by some authors ( Ossom, Evans and Streedharran, 1982).…”
Section: Introductionmentioning
confidence: 99%